Associations between Self-Objectification and Lifestyle Habits in a Large Sample of Adolescents - Migle Baceviciene; Rasa Jankauskiene; Laima Trinkuniene (MDPI AG, 2022)
The aim of the present study was to test associations between self-objectification and health-related lifestyle habits in a large sample of adolescents. In 2019-2020, a large sample of adolescents (n = 1402, 40.4% boys) participated in the survey and, as a part of a larger study, filled in questionnaires on self-objectification and lifestyle. Self-objectification was assessed using the Self-Objectification Questionnaire (SOQ). The lifestyle questionnaire had three batteries: eating attitudes and behaviors, dietary habits, and questions on harmful behaviors together with time spending patterns: sedentary lifestyle and physical activity. The ages ranged from 15-19 years with a mean age of 16.97 ± 0.46 years. Self-objectification (SO) was associated with a less healthy lifestyle: more frequent dieting and unhealthy eating habits in girls, skipping breakfast, and a lower number of meals per day. Adolescent boys and girls with higher SO demonstrated more frequent smoking and alcohol consumption until they felt dizzy and more frequent consumption of soft drinks, energy drinks, and fast foods. Girls with higher SO demonstrated lower perceived physical activity and longer duration of internet browsing for non-educational purposes. The results of the present study inform healthy lifestyle promotion programs for adolescents, suggesting that including psychoeducation about self-objectification, body functionality, and positive embodiment might be an effective strategy.